Social Media in Relationship Marketing: The Professional Sport Context - Abeza, Gashaw (Université d'Ottawa / University of Ottawa, 2016)
The purpose of this thesis is to investigate the use of social media (SM) as a relationship marketing tool (RM) in the context of professional sport in North America. The specific objectives are (i) to explore the use of social media in meeting relationship marketing goals within the context of professional sport, (ii) to explore how professional sport teams’ managers see the opportunities of social media in meeting relationship marketing goals, (iii) to explore how professional sport teams’ managers see the challenges of social media in meeting relationship marketing goals, and (iv) to examine the benefits of social media, if any, in enhancing long-term relationships with their favourite sport team from the perspective of fans of professional sport teams. Guided by a pragmatist philosophical worldview, the project adopted a multi-domain qualitative research approach. The multi-domain approach reflects the three data sources (i.e., the medium-SM platform, organization-professional teams, and consumers-sport fans). Putting an individual emphasis on each of these three data sources, three different but interrelated studies are conducted to accomplish the overall purpose of the dissertation using an article-based format. The first study, guided by the relationship marketing theoretical framework, adopted a netnographic method to investigate professional sport teams’ use of Twitter as an RM tool. Specifically, the study focused on the three core components of RM: communication, interaction, and value. The netnography is based on data gathered from the official Twitter account of 20 professional sport teams from the four major leagues from August 1, 2015 to February 29, 2016. Results outline seven emergent communication types, six interaction practices, and ten values (co)created by the teams or/and fans. Theoretical and practical implications, as well as impetus for future research are identified. The second study aimed at obtaining a first-hand and an in-depth understanding of the role, opportunities, and challenges of SM in meeting RM goals from the perspective of senior managers of professional sport teams. For this purpose, semi-structured interviews were conducted with 26 managers from the four major leagues professional sport teams in North America. Results outline the platforms adopted, six intended objectives, seven opportunities and seven challenges of SM as an RM medium. A list of theoretical and practical implications, and impetus for future research is provided. The purpose of the third study was to first gain an empirically supported understanding of the role and benefits of SM as an RM tool from the perspective of professional sport fans and, following that, to identify, specify, verify, and refine the emergent benefits. The study employed an adaptation of the focus group method, dubbed the ‘sequential funnel-based focus group’, which is a multiphase, step-wise version of the established method. The sequential funnel-based focus group is conceptualized, developed, described, and used in this work as a research method. The adaptation allowed the identification of benefits of SM as a medium that enhances long-term relationships through a series of funnel-based focus group discussions in three sequential phases. A total of 10 focus groups with 81 participants took part in the study. The work identified seven major benefits (and 15 sub-categories of benefits) that fans see as opportunities presented by SM as a medium to enhance long-term relationship with their team. Theoretical contributions, practical recommendations, and directions for future research are provided. The findings from the three studies are integrated to construct a multi-dimensionally informed and comprehensive understanding of the use of SM in RM in professional sport. In general, data gathered from the perspective of the three domains (i.e., medium/SM platform, organizational/ professional teams, and consumers/sport fans) informed that SM is providing new directions to RM, making it an effective and affordable channel in realizing RM goals in professional sport context. The thesis also produced empirical evidence of the opportunities that SM presents and the challenges that it poses in terms of meeting RM goals in the context of professional sport. Informed by the studies data, the dissertation also extended Grönroos’s (2004) RM process model through the lens of SM in professional sport context. Contributions to scholarship, practical recommendations, directions for future research, and the limitations of the dissertation are provided.
Keywords: Interaction; Value; Communication; Relationship; Twitter; Social media use; opportunities and challenges; professional sport; Focus Group; Fans; Netnography; Sequential Funnel-Based; Major league; Professional sport; Focus Group Design